2020
DOI: 10.1515/nf-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Stress modulation of fear and extinction in psychopathology and treatment

Abstract: The glucocorticoid cortisol, a major player in the development of stress-related psychopathology, can also be used for the augmentation of extinction-based psychotherapies (e.g., exposure therapy). Substantial evidence supports its beneficial effects in the treatment of post-traumatic stress disorder and specific phobias. In this review, we first present the role of stress and cortisol in the development of maladaptive emotional memories. Then, we describe the mechanisms that may account for the cortisol-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
2
2
Order By: Relevance
“…4b) and without influences of group (ps>.30). Hence, the sCORT analyses only corroborate a previously reported positive influence of HPA axis activity on extinction consolidation 35,40 , but do not speak for an interaction with dopamine levels.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…4b) and without influences of group (ps>.30). Hence, the sCORT analyses only corroborate a previously reported positive influence of HPA axis activity on extinction consolidation 35,40 , but do not speak for an interaction with dopamine levels.…”
Section: Resultscontrasting
confidence: 71%
“…4b) and without influences of group (ps>.30). Hence, the sCORT analyses only corroborate a previously reported positive influence of HPA axis activity on extinction consolidation 35,40 , but do not speak for an interaction with dopamine levels. sAA and sCORT originate from two different stress systems, the first being faster and more sensitive in responding to stressors, while the second responds more slowly and to more stressful tasks.…”
Section: Relationship Between Salivary Alpha-amylase and Cortisol Lev...contrasting
confidence: 73%
See 1 more Smart Citation
“…Where: Norepinephrine," also identified as noradrenaline," is a "hormone" released by the "adrenal glands," and it is also a "neurotransmitter chemical messenger" that helps transmit nerve signals across nerve cells, muscle cells, or gland cells. "Norepinephrine" travels directly and indirectly to the brain, influencing learning and memory processes, and is involved in the initiation and maintenance of "fear" and "anxiety", modulating "episodic memory", fear conditioning, and fear reconsolidation [14]. "Adrenaline", also known as "epinephrine," is a hormone produced by the "adrenal medulla" inside the "adrenal glands".…”
Section: Endocrine Systems Glands That Release Stress Hormonesmentioning
confidence: 99%
“…1c ). The activity of these systems, linked to arousal and stress, have been suggested to affect consolidation processes in general and extinction consolidation in particular 33 35 . We had previously observed L-DOPA main effects in two out of three MRI experiments 14 , 16 , 17 , while two purely behavioral experiments showed only conditional L-DOPA effects, moderated by prior extinction success 18 , and one other behavioral study showed no significant effect 19 .…”
Section: Introductionmentioning
confidence: 99%